2003
DOI: 10.1530/eje.0.1480579
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cAMP response element-binding protein and sodium iodide symporter in benign non-functioning and malignant thyroid tumours

Abstract: Objective: Reduced expression or defective targeting of the sodium/iodide symporter (NIS) to the cell membrane in thyroid tumours has been reported. The expression of the NIS gene is up-regulated by TSH through the cAMP pathway and the characterization of the promoter region of the rat NIS gene revealed the existence of a degenerate cAMP response element (CRE) sequence. The cAMPdependent transcription factor cAMP response element-binding protein (CREB) binds to CRE acting, upon phosphorylation, as a transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Surprisingly, the levels of specific CREB1 mRNA were lower in PTCs compared with normal thyroid (Supplementary Figure 3). Analogous results have been described earlier (Luciani et al, 2003). Post-translational mechanisms, therefore, account for the increased CREB1 protein levels in PTCs.…”
Section: Ccdc6 Inhibits Creb1 Activity Also In Human Ptcssupporting
confidence: 88%
“…Surprisingly, the levels of specific CREB1 mRNA were lower in PTCs compared with normal thyroid (Supplementary Figure 3). Analogous results have been described earlier (Luciani et al, 2003). Post-translational mechanisms, therefore, account for the increased CREB1 protein levels in PTCs.…”
Section: Ccdc6 Inhibits Creb1 Activity Also In Human Ptcssupporting
confidence: 88%
“…By contrast, several other studies have shown either normal, or even increased levels of NIS mRNA (Arturi et al, 1998;Luciani et al, 2003;Saito et al, 1998;Tanaka et al, 2000) or protein (Dohan et al, 2001;Saito et al, 1998;Wapnir et al, 2003) expression in thyroid cancer. However, immunohistochemical analyses have detected NIS protein that was not located predominantly in the basolateral membrane, as found in normal thyroid tissue, but was principally in the cytoplasm (Castro et al, 1999b;Dohan et al, 2001;Wapnir et al, 2003).…”
Section: Discussionmentioning
confidence: 65%
“…CREB has been shown to be involved in leukemogenesis (Perissi et al, 1999;Shankar and Sakamoto, 2004), human melanoma cell survival (Jean et al, 1998) and several endocrine tumors (Habener et al, 1989;Peri et al, 2002;Rosenberg et al, 2002a, b;Luciani et al, 2003). Also, inhibition of Erk1/Erk2 and CREB phosphorylation can inhibit growth and induce apoptosis in cells derived from human fibrosarcoma (Rabelo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%